2023
DOI: 10.3390/molecules28031176
|View full text |Cite
|
Sign up to set email alerts
|

Lavandula angustifolia Essential Oils as Effective Enhancers of Fluconazole Antifungal Activity against Candida albicans

Abstract: The increasing prevalence of Candida albicans resistance to commercial antifungal agents in recent decades has prompted modern medicine and veterinary medicine to search for combined treatment options. The aim of the study was to determine the activity of essential oils from different cultivars and morphological parts of the medicinal lavender (Lavandula angustifolia) in combination with fluconazole against Candida albicans ATCC 10231 strain. The effect of the combination of lavender essential oil with flucona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The chemical composition of lavender essential oils was presented in our previous publication [29]. The main chemical components detected in the essential oils from the flowers of L. angustifolia were linalyl acetate (17.8-31.0%) and linalool (28.5-33.0%), while lavandulol acetate, borneol and caryophyllene oxide were present in lower concentrations (<5%).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The chemical composition of lavender essential oils was presented in our previous publication [29]. The main chemical components detected in the essential oils from the flowers of L. angustifolia were linalyl acetate (17.8-31.0%) and linalool (28.5-33.0%), while lavandulol acetate, borneol and caryophyllene oxide were present in lower concentrations (<5%).…”
Section: Resultsmentioning
confidence: 97%
“…After storage in the refrigerator for 24 h, the drying agent was removed by filtration and the solvent was evaporated to obtain a pure essential oil. All isolated essential oils were analyzed using gas chromatography with mass selective detector (GC-MS), what was described previously [29]. (See Supplementary Materials for details).…”
Section: Isolation Of Essential Oilsmentioning
confidence: 99%
“…In general, the amounts of EO produced by the plants are generally below 2% (Boukhatem et al 2019), which is similar to the results in this study. Previous studies (Carrasco et al 2015;Tardugno et al 2018;and Adaszyńska-Skwirzyńska et al 2023) reported that the yields of lavender EO were 1.5%, 1.67%, and 1.92%, respectively. Similarly, Elharas et al (2013) reported that Moroccan lavender yields 1.5% lavender EO.…”
Section: Extraction Kinetics and Yield Of Essential Oil Of Lavandula ...mentioning
confidence: 94%
“…"As a dispersion media, the solvent might be an aqueous, organic, inorganic, or a combination of solvents" [9,10,11, 11a,11b,11c]. "Topical gels are applied to the skin to act as a contact or transport medium for active medications" [12,13,14,15]. The gel's three-dimensional mesh entangles the active drug molecules.…”
Section: Introduction Of Antifungal Topical Gelmentioning
confidence: 99%